“34 Preludes and Fugs” by Valentin Bibik: nnovative Features in Realization of the Compositional-Dramaturgical Concept of the Great Polyphonic Cycle - Postovoitova, Svetlana (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2022)
Relevance of the article. In 1978, Valentin Savich Bibik completed his work on the monumental polyphonic cycle “34 Preludes and Fugues” opus 16, he began working on it in 1973. This composition is a continuation of the composer’s work in the polyphonic genre: in 1968, the cycle “24 Preludes and Fugues” opus 2 was written, and in 1970 two preludes and fugues opus 7 were written. A significant motivating factor for a detailed study of the “34 Preludes and Fugues” is the original musical language, the tonal, metro-rhythmic and thematic organization of the cycle. They radically distinguish it from the works of other composers in this genre. The insufficiently studied polyphonic works of Valentin Bibik determine the relevance of this study. Purpose of the article. To identify innovative features of the implementation of the compositional and dramatic concept in the cycle “34 Preludes and Fugues” by V. Bibik. Scientific novelty. In studies devoted to "34 Preludes and Fugues" by V. Bibik, the features of the innovations of this cycle (avant-garde techniques, the complexity of the musical language) are only ascertained; the fact of connection with Bach’s traditions is mentioned. The deep processes involved in the formation of the integrity of a large polyphonic means as well as the levels of embodiment of the composer’s concept of the cycle remained hidden behind the descriptive presentation of the fact. The article traces and formulates for the first time the main features of composer innovation in the framework of the compositional and dramatic concept of a large polyphonic cycle. The research methodology includes the use of systemic and functional methods. Main results and conclusions. V. Bibik’s “34 Preludes and Fugues” demonstrate an innovative version of the interpretation of the polyphonic cycle, due to the original combination of modern techniques with polyphonic principles and methods of development. The most significant innovations in the cycle are the rejection of the functionally centralized ladotonal system, the original interpretation of metrorhythmic organization and the specifics of the theme, which, in turn, led to significant transformations at all stages of fugue formation. In addition to these features of innovation, the cycle has deep internal connections between the elements, from the moment of creating the theme to the formation of the integrity of the cycle.